Type I IFN signaling shapes subset-specific monocyte fates in the injured myocardium - Ecem Tugba Sakalli; Giuseppe Rizzo; Alma Zernecke; Gustavo Campos Ramos (Journal of Clinical Investigation, 2026)
Monocytes and macrophages promote tissue repair following myocardial infarction, but the mechanisms tuning their effector functions remain elusive. While macrophages are essential in clearing debris and resolving inflammation, they can also contribute to uncontrolled inflammation and provoke additional damage. Thus, factors that influence macrophage differentiation trajectories and phenotypes play an important role in cardiac repair outcomes. By combining genetic lineage tracing with cell-specific targeting, the study from Koenig et al. sheds light on key signaling events that shape monocyte fate decisions in the injured myocardium, establishing a differentiation hierarchy among monocyte-macrophage subsets. The findings also reveal that macrophages with an IFN response signature give rise to MHCII hi macrophages, which, in turn, contribute to regulatory T cell generation and cardioprotection. This work underscores the importance of understanding cardiac macrophage phenotypic plasticity within a broader framework of lineage relationships.